(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. End-stage renal disease is a serious illness with major consequences in both health and healthcare expenditures. The growing number of patients with end-stage renal disease in developing countries will consume a greater proportion of healthcare budget. We aimed to assess the costs of hemodialysis and kidney transplantation in a renal care center in Sudan. Materials and Methods. We conducted a cross-sectional study to estimate the costs of kidney transplantation and compare those with the costs of hemodialysis per year. We enrolled 78 patients on regular hemodialysis for at least 2 years and 33 kidney transplant patients on regular follow-up at Gezira Hospital for Renal Diseases and Surgery in Sudan. Results. The annual cost of hemodialysis was found to be US 6847.00. The total cost of the first year after transplantation was US 14 825.04 and the cost of kidney transplantation after the first year was US 10 651.00. The total hospitalization days and absence from work were less in the transplant group. Conclusions. Hemodialysis in Sudan is less expensive than transplantation.